Pengaruh Free Cash Flow, Profitabilitas, dan Likuiditas terhadap Kebijakan Dividen : (Studi Empiris pada Perusahaan Farmasi & Kimia yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021) - Martin Martin; Amin Hou; Fauzia Mei Salsabila (Universitas Kristen Indonesia Toraja, 2023)
This study aims to analyze the effect of free cash flow, profitability, and liquidity on dividend policy in pharmaceutical and chemical companies listed on the Indonesia Stock Exchange (IDX) during the period 2017-2021. Dividend policy is one of the important decisions in a company that can affect shareholder satisfaction and market performance. The method used in this study is multiple regression analysis to identify the relationship between independent variables (free cash flow, profitability, and liquidity) and dependent variables (dividend policy). The data used were taken from the annual reports of companies listed on the IDX in the pharmaceutical and chemical sectors. The results of the study indicate that free cash flow and profitability have a significant effect on dividend policy, while liquidity does not have a significant effect. This finding indicates that pharmaceutical and chemical companies tend to provide dividends based on their available cash surplus and their level of profitability, while liquidity is not a major determinant in their dividend policy. This study provides additional insight for corporate managers and investors regarding the factors that influence dividend decisions in the pharmaceutical and chemical industries.